Ultrasonic Dissection versus Conventional Dissection for Pancreatic Surgery: A Meta-Analysis - Haiming Lei; Dong Xu; Xinghua Shi; Koulan Han (Gastroenterology Research and Practice)
Background. The role of ultrasonic dissection (UD) in pancreatic surgery remains controversial. The aim of this meta-analysis was to evaluate the clinical effect of UD in pancreatic surgery when compared with conventional dissection (CD). Materials and Methods. A comprehensive literature search was performed to identify eligible studies that compared UD with CD for pancreatic surgery in PubMed, EMBASE, Web of Science, and the Cochrane Library. Risk ratio (RR) or mean difference with 95% confidence interval (CI) was calculated. Results. Six studies were included with a total of 215 patients undergoing UD and 210 undergoing CD. In comparison with CD in distal pancreatectomy, UD was associated with lower rates of pancreatic fistula (RR = 0.46, 95% CI: 0.27–0.76) and abdominal abscess and shorter operation time and hospital stay (P<0.05). In pancreaticoduodenectomy, there was no significant difference in pancreatic fistula rate between two groups (RR = 0.79, 95% CI: 0.48–1.29). However, the significantly less intraoperative blood loss and the transfused blood unit were found in patients receiving UD (P<0.05). Conclusions. The results of this meta-analysis show that, in comparison with CD, UD is associated with better perioperative outcomes in pancreatic surgery.